Increased Postoperative Day One Discharges After Implementation of a Hysterectomy Enhanced Recovery Pathway. Issue 8 (August 2015) - Miller, Elizabeth C.; McIsaac, Daniel I.; Chaput, Alan; Antrobus, Jonathan; Shenassa, Hassan; Lui, Anne
<x xml:space="preserve">Abstract</x> ABSTRACT Enhanced recovery or "fast-track" programs that optimize perioperative care have been effective in improving outcomes after colorectal and orthopedic surgery. These programs accelerate recovery, reduce morbidity, and shorten the hospital length of stay (LOS). Benefits of enhanced recovery following gynecologic surgery have been less clearly defined. The primary barriers to early discharge from the hospital for open hysterectomy and myomectomy patients include pain, nausea and vomiting, ileus, inability to mobilize, and sedation. The hysterectomy enhanced recovery (HER) pathway is an evidence-based, multidisciplinary, and multifaceted intervention for perioperative care for women with benign disease undergoing elective open surgery. The HER pathway was introduced in 2011 at Ottawa Hospital (TOH), a large tertiary-care center. The aim of HER was to improve perioperative quality of care and target discharge on postoperative day (POD) 1 when appropriate. This retrospective before-and-after cohort study tested the hypothesis that implementation of the HER pathway during the perioperative period would result in an increased POD 1 discharge rate among women undergoing elective open hysterectomy and myomectomy, The pre-HER group was composed of patients undergoing surgery between July 2011 and September 2012, and the post-HER group included patients whose surgery took place between July 2011 and September 2012. Patients with chronic pain and nonelective surgery were excluded. Data were obtained from medical chart review. The primary outcome was the percentage of POD 1 discharges. Secondary outcomes included a combination of return to the emergency department or to the hospital within 30 days of discharge, median LOS, clinician compliance with HER, and an exploratory analysis with multivariable modeling to determine which aspects of the HER were independently associated with POD 1 discharge. Variables in the multivariable model included American Society of Anesthesiologists physical status (≥II), history of prior abdominal surgery, body mass index, type of anesthesia, and provision of a transversus abdominis plane block. A total of 223 patients met eligibility criteria: 100 pre-HER and 123 post-HER. A higher percentage of patients in the post-HER group were discharged on POD 1 than in the pre-HER group (34% vs 7%); the adjusted odds ratio (aOR) was 7.33, with a 95% confidence interval (CI) of 3.05 to 17.62, P < 0.001. The combined rates of early readmission to the hospital and early return for emergency care were similar in the 2 groups (10% post-HER vs 13% pre-HER; aOR, 0.74; 95% CI, 0.32–1.74). The median LOS was 3 days in the pre-HER group and 2 days in the post-HER group (P < 0.0001). In exploratory analysis, only inhaled general anesthesia was independently associated with decreased odds of POD 1 discharge (aOR, 0.16; 95% CI, 0.04–0.65; P = 0.01). Implementation of the HER pathway for patients undergoing elective open nonmalignant gynecologic surgery is associated with a higher POD 1 discharge rate, without increasing the combined rate of early return to the hospital and emergency care.